Application of the coaching biomechanics interface: which technique should I choose? - Hiley, M. J.; Hall, P.; Yeadon, M. R.; Irwin, G. (Sports Biomechanics, 2025)
The undersomersault (Felge) is one of the key family of skills on the parallel bars in men`s artistic gymnastics. At the highest level of competition, two distinct techniques, termed here `deep pike` and `hips close`, are used to perform the skill. The aim of the present study was to determine the relative performance benefits of each technique in order to provide coaches with information to facilitate technique selection and gymnast preparation. A combination of kinematic analysis of Olympic performances and technique optimisation using computer simulation modelling was used to address this aim. The kinematic analysis found that both techniques had similar performance outcomes in terms of generating horizontal and vertical velocity at release, confirming that both techniques were fit for purpose. Results from the optimisation study found that the `deep pike` had an advantage in generating vertical velocity, due to more time to perform work, and being more forgiving in terms of generating a larger release window for acceptable performance, whilst the `hips close` technique was associated with requiring less effort (sum of joint torques squared). As the `deep pike` requires more effort and a larger range of hip flexibility, choosing this technique will have implications for gymnast preparation.